Hubungan Antara Persepsi-Keadilan, Kepercayaan dan Komitmen dari Konsumen Pengadu-Keluhan - Leokadia Retno Adriani (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Complaint is a form of consumer complain behavior. Complainants evaluate their complaining experience by their perceived-justice, which will influence their satisfaction, trust and commitment to the firm. This research finds that cellular-phone operator complainant's perceived-justice has the effect on complainant's trust and commitment, with satisfaction as an intervening variable.